Comment on “The early origin of a birdlike inner ear and the evolution of dinosaurian movement and vocalization” - David, R; Bronzati, M; Benson, RBJ (American Association for the Advancement of Science, 2022)
Hanson et al. (Research Articles, 7 May 2021, p. 601) claim that the shape of the vestibular apparatus reflects the evolution of reptilian locomotion. Using biomechanics, we demonstrate that semicircular canal shape is a dubious predictor of semicircular duct function. Additionally, we show that the inference methods used by Hanson et al. largely overestimate relationships between semicircular canal shape and locomotion.